Analytical fragility curves for masonry school building portfolios in Nepal - Nicola Giordano; Flavia De Luca; Anastasios Sextos (Bulletin of Earthquake Engineering, 2021)
Schools represent a reference point for communities in any part of the world. Therefore, their safety and resilience against natural catastrophes is of paramount importance. The recent 2015 Gorkha earthquake has unfortunately shown that Nepalese school buildings are highly vulnerable to seismic actions. Most of them are indeed constituted by low-quality unreinforced masonry (URM). The quantification of URM vulnerability is fundamental to estimate the risk associated to school building portfolios at territorial scale. This work discusses statistics available for Nepalese schools and then presents analytical fragility curves for three recurrent URM typologies covering more than 50% of the school building stock. The methodology adopted to derive fragilities is spectral-based and accounts for out-of-plane and in-plane damage potential in a single easy-to-use analytical framework. Inter-building, intra-building and record-to-record variabilities are directly considered in the analysis. The obtained fragilities integrate the studies available for the region and can be used for pre-/post-earthquake risk assessment and prioritization of interventions at country level.